Remarks on the prescriptions and the dispensing of the medications - Khalid Al Aboud (Our Dermatology Online, 2014)
Several researchers have called for reforms in drug naming, labeling, and packaging standards. Giving the patients the medications remains the most important stage in patients care. There are medical errors associated with this stage. In the following disquisition, we shall highlights on some points on the prescriptions and the dispensing of the medications. We wish that these points encourage further discussions by the readers.